1997
DOI: 10.1007/s004220050320
|View full text |Cite
|
Sign up to set email alerts
|

Two-arm trajectory planning in a manipulation task

Abstract: This paper addresses the trajectory planning problem for a task which requires positioning and orienting an object firmly grasped by two hands at a visually specified goal configuration in the horizontal plane. The motor task involves three degrees of freedom (two translational and one rotational), and the motions of the arms are constrained by the physical coupling through the held object. Experimentally measured trajectories of two arms in the coordinated positioning/orienting task are presented. The hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In this manner, the similar modulation at the wrist and elbow joints suggests that control of the two joints are linked, probably neurally and anatomically. A separate and parallel control of the wrist may arise when inertially uncoupled motions, such as pronation and supination, are important for orientation of the hand (Desmurget et al 1996;Garvin et al 1997;Lacquaniti and Soechting 1982;Sergio and Ostry 1995;Soechting and Flanders 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In this manner, the similar modulation at the wrist and elbow joints suggests that control of the two joints are linked, probably neurally and anatomically. A separate and parallel control of the wrist may arise when inertially uncoupled motions, such as pronation and supination, are important for orientation of the hand (Desmurget et al 1996;Garvin et al 1997;Lacquaniti and Soechting 1982;Sergio and Ostry 1995;Soechting and Flanders 1993).…”
Section: Discussionmentioning
confidence: 99%
“…One may speculate that it takes longer time to acquire a unique profile for the normal force. On the other hand, it should be noted that somewhat similar phenomenon can be observed in cooperative bi-manual manipulations (Zefran et al, 1995;Garvin et al, 1997). The tangential component of the hand contact force is directly linked to the crank-rotation while the normal component only influences the movement indirectly through the internal muscle force equilibrium of the arm.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 79%
“…Studies to investigate human dual-arm manipulation tasks have been previously reported [6,7]. However, few studies directly address the trajectory formation and force distribution of the dual-arm task, especially in dynamical environments [7].…”
Section: Movement Involving Two Armsmentioning
confidence: 99%